2010
DOI: 10.1007/s10856-010-4057-x
|View full text |Cite
|
Sign up to set email alerts
|

In vitro biocompatibility and corrosion resistance of a new implant titanium base alloy

Abstract: One objective of this work was to study the corrosion resistance of the new implant Ti-10Zr-5Ta-5Nb alloy in physiological fluids of different pH values, simulating the extreme functional conditions. Another objective was in vitro biocompatibility evaluation of the new alloy using human fetal osteoblast cell line hFOB 1.19. Cytocompatibility was assessed by determination of possible material cytotoxic effects, cell morphology and cell adhesion. The thermo-mechanical processing of the new implant alloy consiste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 39 publications
0
22
0
Order By: Relevance
“…A difference in bone formation around implants of pure Ti, hafnium (Hf), rhenium (Re), Nb and Ta in vivo using a rat model has been shown, where greater bone area was observed for Nb, Ta and Re as compared to Ti after 4 weeks [19]. The biocompatibility of Ti, Zr, Nb and Ta is well documented in the literature [18][19][20] and in agreement with the results of the present study where neither the Ti nor the Ti-Ta-Nb-Zr material showed any sign of cytotoxicity or adverse tissue reactions. The metal release of Zr-Nb-Ta-alloyed Ti compared with that of Ti-Al-V has been evaluated both in vitro [53] and in a rat model up to 48 weeks in vivo [54], showing very low metal release for the Ti-, Zr-, Nb-and Ta-containing material, indicating that it may be advantageous for long-term implantation.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…A difference in bone formation around implants of pure Ti, hafnium (Hf), rhenium (Re), Nb and Ta in vivo using a rat model has been shown, where greater bone area was observed for Nb, Ta and Re as compared to Ti after 4 weeks [19]. The biocompatibility of Ti, Zr, Nb and Ta is well documented in the literature [18][19][20] and in agreement with the results of the present study where neither the Ti nor the Ti-Ta-Nb-Zr material showed any sign of cytotoxicity or adverse tissue reactions. The metal release of Zr-Nb-Ta-alloyed Ti compared with that of Ti-Al-V has been evaluated both in vitro [53] and in a rat model up to 48 weeks in vivo [54], showing very low metal release for the Ti-, Zr-, Nb-and Ta-containing material, indicating that it may be advantageous for long-term implantation.…”
Section: Discussionmentioning
confidence: 89%
“…Significantly higher bone-implant contact was also observed for Ti and Ta as compared to the other metals at 4 weeks [19]. A binary alloy consisting of Ti and 8 at% Zr is in clinical use and has shown good biocompatibility [20] and osseointegration [21]. This alloy performed in a similar manner to Ti in vitro, in vivo and clinically, but long-term clinical evaluation is yet lacking [22].…”
Section: Introductionmentioning
confidence: 99%
“…The spectra were acquired in the 10 5 -10 À1 Hz frequency range. The impedance spectra were displayed as Nyquist and Bode (phase angle vs. frequency) diagrams [29][30][31][32].…”
Section: Methodsmentioning
confidence: 99%
“…VoltaMaster 4 program directly supplies the values of the corrosion current density, i corr , corrosion rate, V corr and polarisation resistance, R p . Ion release rates were calculated [29][30][31][32].…”
Section: Methodsmentioning
confidence: 99%
“…Ti-10Zr-5Ta-5Nb alloy was modified by hot rolling accompanied with heat treatment and the biocompatibility of modified surface was examined. The results suggested that there is no effect on cell viability of human fetal osteoblast cell line hFOB 1.19 and the corrosion resistance was improved with increased biocompatibility 69 . The surface morphology of alkali-heat treated Ti-27Nb alloy was characterized via SEM, XRD.…”
Section: Alkali-heat Treatmentmentioning
confidence: 96%